Application of NTC Techniques and Games in Teaching Mathematical Content in Primary Education - Bobić, Slavica; Rajović, Vuk; Vesić, Dragana; Šuvira, Jelena; Mrđa, Mirela (Norma, 2026)
The development of mathematical literacy in early education represents a key factor for children’s cognitive development and later academic achievement. This paper presents the results of applying games, techniques, and activities from the NTC learning system in teaching mathematics to students from grades 1 to 4. The focus is on the game “ Add a Color to the Number” for practicing arithmetic operations, the board game “Multiplier” for mastering the multiplication table, and the technique of illogical stories for learning Roman numerals. The results show that the use of games and associative learning enables children to acquire knowledge not only mechanically, but through active, meaningful, and emotionally engaging experiences. Particularly significant effects were noticed in learning the multiplication table, where students demonstrated high motivation, success, and the development of strategic thinking. Activities such as addition through associations and learning Roman numerals with illogical stories contributed to creativity and easier mastery of the material.